A System Dynamics Approach to Corn Production in indonesia: Causal Loop Diagram - Asriani Asriani; Dhian Herdhiansyah (Journal of Global Innovations in Agricultural Sciences)
This study investigates the challenges facing corn production in Indonesia, using a system dynamics approach to address its role in national food security. The research focuses on declining domestic corn production, increasing reliance on imports, and limited market availability, all of which pose significant risks to food security. The study's primary objective is to analyze strategies for improving corn production, emphasizing harvested area expansion, productivity enhancements, and their combined effects. Time series data from 1980 to 2019 were sourced from the Central Bureau of Statistics (BPS), the Ministry of Agriculture, the Ministry of Trade, and the Food and Agriculture Organization (FAO). A quantitative descriptive approach was employed, utilizing system dynamics modeling—comprising input-output analysis and causal loop diagrams—to simulate key factors influencing corn production. Model verification was conducted using the Mean Absolute Percentage Error (MAPE) method, and simulations were performed with Powersim software to project future outcomes. The results indicate that without strategic interventions (Scenario 1), corn production is projected to decline to 31,863,838 tons by 2040, with productivity at 4.8 tons/ha, well below the potential 8 tons/ha. Scenario 2, which focuses on expanding harvested area by 3.5% per year while limiting land conversion, shows considerable potential if supported by sound management and policies. Scenario 3 aims to increase productivity to 5.87 tons/ha through advanced agricultural practices, with projected production reaching 44,761,157 tons by 2040. The combined strategy of area expansion and productivity improvement (Scenario 4) could result in corn availability of 15,063,006 tons by 2040. The study concludes that with proper government support, including the formation of farmer institutions, technical and financial assistance, and stronger partnerships between farmers and industry, Indonesia can significantly boost its corn production and enhance national food security. Keywords: Corn production, system dynamics, national food security, agricultural productivity, causal loop diagram